First language attrition : interdisciplinary perspectives on methodological issues - Schmid, Monika S. (Studies in bilingualism ;, 2004)
This volume provides a state-of-the-art treatment of research on language attrition, the non-pathological loss of a language through lack of exposure. It combines a review of past and present research with in-depth treatments of specific theoretical and m.